Microclimate in peach-tea ecosystems and its effect on labour's comfortableness - HUANG Shou-bo; SHEN Chao-dong; CHEN Hai-sheng; FU Mao-yi (浙江大学学报. 农业与生命科学版, 2001)
This paper describes the microclimatic characteristics in peach-tea ecosystems and its effect on labour's comfortableness. The result indicates that the illuminance, air temperature and wind speed in peach-tea ecosystems is lower than that in control tea garden, but air relative humidity is higher than in control one. Working in peach-tea ecosystems, the discomfort index of human body reduced by 3, the time of the most discomfort or heatstroke for all people reduced by 1 h. Due to higher worker's comfortableness in peach- tea ecosystems, the worker's productivity increases around 23%-30%.